EXPLORING EFL STUDENTS' DIFFICULTIES IN MICROTEACHING CLASS (A CASE STUDY OF SIXTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM OF PATTIMURA UNIVERSITY) - Letsoin, Juliana; Lekawael, Rosina; Hukom, Salmon (Pattimura University, 2024)
The aims of this research were to identify the difficulties faced by EFL students in microteaching class, to find out the most significant difficulties and the strategies to overcome the difficulties faced by EFL students in microteaching class for sixth semester students in the English Education Study Program of Pattimura University. To obtain information from EFL students, this research used explanatory mixed method involving questionnaires and interviews to collected the data. The questionnaires are used to answer the identifying students and interviews are used to answer strategies used by students in microteaching classes. The participants of the research were from 37 students of class A in the sixth semester class students of 2020 in academic year 2023/2024, at English Education Study Program, Pattimura University. The results of questionnaires showed that difficulties face by EFL students as prospective teachers in the procedural category 45%, managerial category 65%, psychological category 55%, instructional category 41%, and professional category 29%. While, the result of the interview and questionnaire also showed that most of the EFL students’ difficulty in managerial category. Based on questionnaire result 65% EFL students as prospective teachers had difficulties in managerial category namely difficulty in planning advance the contents of the material, difficulty in explaining the material to the participants, difficulty in managing the classrom, difficulty in using series of teaching strategies according to strategy planning and material and difficulty in controlling the class activity. While, based on interview result students mentioned that they had difficulties also in managerial category namely difficulty in using series of teaching strategies and explaining the material. The strategies that EFL students used to overcome their difficulties based on interviews results are more practice, time management, discuss with the lecturer and friends, watching videos on the internet/YouTube, and learn more. Most of them always practice more to overcome their difficulties in microteaching classes.